An imaginative approach to teaching - Egan, Kieran (San Francisco, CA : Jossey-Bass, 2005)
Provides a unique approach to the theory of K-12 education, with an emphasis on the use of imagination and emotion as powerful tools to enhance cognitive development.
Includes bibliographical references (p. 235-236) and index.
Choice.
Reference and Research Book News.
Professional
Keywords: Creative thinking -- Study and teaching; Imagination in children; Teaching; Creative thinking -- Study and teaching; Imagination; Teaching